Comparison of the Effectiveness of Metacognitive Therapy with Emotion-Focused Therapy on Fear of Intimacy and Social Intimacy in Divorced Women - Heydari Faela, Firouze; Atashpour, Seyyed Hamid; Khayatan, Floor (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to compare the effectiveness of metacognitive therapy and emotion-focused therapy on reducing fear of intimacy and increasing social intimacy among divorced women. Methods and Materials: The research design was quasi-experimental with a pretest, posttest, and a 45-day follow-up using experimental and control groups. The statistical population included all divorced women residing in Shiraz in 2021, from whom 60 participants were selected via purposive sampling and assigned to three equal groups of 20 participants each. Therapeutic interventions for both approaches were conducted over 10 weekly sessions, each lasting 90 minutes. The control group did not receive any intervention. Data were collected using the Fear of Intimacy Questionnaire (Descutner & Thelen, 1991) and the Social Intimacy Scale (Miller & Lefcourt, 1982), and analyzed via repeated-measures analysis of variance in SPSS version 23. Findings: The findings indicated that both therapeutic approaches significantly reduced fear of intimacy and increased social intimacy in divorced women during the posttest and the 45-day follow-up. Bonferroni post-hoc tests showed that metacognitive therapy was more effective than emotion-focused therapy in enhancing social intimacy (p < .05), although no significant difference was found between the two therapies in regard to fear of intimacy. Conclusion: The results of this study provide empirical support for both therapeutic approaches in improving intimacy indicators among divorced women and suggest that family and marital therapists’ awareness of these methods may be beneficial.